Preparation method of aluminum-containing SiBCN ceramic fiber
By using polyaluminum carbosilane and boron nitride powder to prepare PACS/BN hybrid pioneers and performing specific process processing, the complex operation and material safety problems of preparing SiBCN ceramic fibers in the prior art are solved, and efficient densification of ceramic fibers and adjustability of boron nitrogen content are achieved.
Patent Information
- Application Number
- CN202510216102.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-06-27
- Estimated Expiration
- 2045-02-26
AI Technical Summary
In the prior art, when preparing heterogeneous element SiBCN ceramic fibers, there are problems with the use of toxic organic raw materials, long reaction time, cumbersome operation and difficult to obtain PBSZ.
Polyaluminum-carbonsilane and boron nitride powder were used as raw materials to prepare PACS/BN hybrid pioneers by ball milling blending, and aluminum-containing SiBCN ceramic fibers were prepared through melt spinning, non-melting treatment, high-temperature pyrolysis and sintering density processes.
It achieves simple operation, mild reaction conditions, avoiding the use of toxic organic raw materials and PBSZ, and the boron nitrogen content of ceramic fibers is adjustable and the density is improved.
Smart Images

Figure CN120210991A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of precursor conversion ceramic fibers, and particularly relates to a preparation method of aluminum-containing SiBCN ceramic fibers. Background Art
[0002] Continuous fiber reinforced ceramic matrix composites have excellent properties such as high specific strength, high specific modulus, high toughness, high temperature resistance and ablation resistance, and are widely used in high-tech fields such as aerospace. With the development of space exploration technology, the requirements for the properties of ceramic matrix composites (such as high temperature resistance, oxidation resistance, etc.) are getting higher and higher, and ceramic fibers have become the key to preparing high-performance ceramic matrix composites. Silicon boron carbon nitride (SiBCN) fibers have received extensive attention in the military or civilian fields due to their good high-temperature thermal stability and good high-temperature oxidation resistance. However, in a high-temperature oxidation environment, boron (B) in the SiBCN ceramic material will form boron trioxide (B2O3) gas and volatilize, thereby weakening its high-temperature resistance and oxidation resistance. Elements such as aluminum (Al), zirconium (Zr), and hafnium (Hf) are introduced into the SiBCN ceramic material to form a multi-element system, thereby improving the comprehensive properties of the ceramic material.
[0003] At present, the key to preparing SiBCN ceramic fibers containing heteroelements lies in precursor synthesis. Polyborosilazane (PBSZ) precursors containing heteroelements are generally obtained through two approaches: (1) reacting the raw materials for synthesizing PBSZ with reagents containing specific elements; (2) directly reacting PBSZ with reagents containing specific elements.
[0004] Among them, PBSZ containing heterogeneous elements is obtained by reacting the raw materials for synthesizing PBSZ with a reagent containing specific elements. For example, Liu Yong et al. (Patent Application Publication No.: CN107500766A) disclosed the preparation of amorphous silicon boron carbon nitride zirconium ceramic fibers. The synthesis method of the precursor is as follows: Under the condition of a temperature lower than -10°C and in a nitrogen atmosphere, a mixed solution of boron trichloride and chlorosilane is first added to a hexamethyldisilazane solution and stirred for 8 to 16 hours, then stirred at 120 to 150°C for 3 to 4 hours, and cooled to room temperature to obtain a light yellow liquid; zirconium dichloride bis(acetylacetonate) (Zr(AcAc)3) is added to the light yellow liquid, heated to 170 - 190°C and stirred for 4 to 6 hours, and then heated to 220 to 250°C and stirred for 4 to 6 hours to obtain a yellow precursor. This method for synthesizing the precursor requires the use of toxic organic raw materials, has a long reaction time, harsh reaction conditions, and cumbersome operations, etc.; while PBSZ directly reacts with a reagent containing specific elements to obtain PBSZ containing heterogeneous elements. For example, Du Liang et al. (Patent Application Publication No.: CN105801866A) disclosed the preparation of an aluminum-containing polyborosilazane ceramic precursor. The method is to first dissolve solid PBSZ in xylene, and then add an organometallic aluminum reagent (such as aluminum sec-butoxide, aluminum acetylacetonate, etc.), heat to 100 - 130°C and react for 2 - 3 hours, and then heat to 150°C and reflux for 2 - 3 hours. After the reaction, the solvent is removed to obtain a yellow solid aluminum-containing PBSZ, but this invention does not involve whether it can be spun later and the preparation of aluminum-containing SiBCN ceramic fibers. Wu Baolin et al. (Patent Application Publication No.: CN109825901A) disclosed aluminum- and zirconium-codoped silicon carbide / boron nitride fibers and their preparation method. The preparation method of the precursor is as follows: Aluminum acetate, Zr(AcAc)3 and PBSZ are fully mixed in a high-pressure reaction kettle, and then polydimethylsiloxane (PDMS) is injected and evenly covered on the surface of the mixture, heated to 180°C and kept warm for 2 hours to obtain a crude material; the crude material is dissolved in xylene, filtered, and distilled under reduced pressure to obtain a fine material of aluminum- and zirconium-codoped silicon carbide / boron nitride precursor. The whole reaction is carried out in a high-pressure system and PBSZ is difficult to synthesize.
[0005] In summary, there are still certain technical difficulties in preparing a precursor containing heterogeneous elements by using organic raw materials or PBSZ to prepare the corresponding SiBCN ceramic fibers, which are mainly manifested as follows: (1) The organic raw materials are highly toxic; (2) The operation is cumbersome and the reaction time is long; (3) The reaction conditions are harsh (low temperature or high-pressure environment); (4) PBSZ is difficult to obtain. Summary of the Invention
[0006] To solve the problems existing in the background art, the purpose of the present invention is to provide a preparation method of aluminum-containing SiBCN ceramic fibers. This method has the advantages of simple operation, mild reaction conditions, avoiding the use of highly toxic organic reagents (such as boron trichloride, chlorosilane, and hexamethyldisilazane, etc.) or using difficult-to-obtain PBSZ as raw materials for aluminum doping modification, and having adjustable boron and nitrogen contents and densification in ceramic fibers.
[0007] The technical solution adopted by the present invention is as follows:
[0008] I. A preparation method of aluminum-containing SiBCN ceramic fibers:
[0009] (1) Preparation of the hybrid precursor: Dissolve a certain proportion of polyaluminum carbosilane (PACS) in a solvent to form a polyaluminum carbosilane solution, add boron nitride powder (BN), and place it in a ball mill jar for ball milling for a certain time. After the boron nitride powder is uniformly dispersed in the polyaluminum carbosilane solution, distill off the solvent to obtain a uniform light yellow PACS / BN hybrid precursor;
[0010] (2) Sequentially perform four processes of melt spinning, infusibilization treatment, high-temperature pyrolysis, and sintering densification on the PACS / BN hybrid precursor in step (1) to obtain black aluminum-containing SiBCN ceramic fibers.
[0011] The polyaluminum carbosilane in step (1) is directly polymerized from low molecular weight polycarbosilane and aluminum acetylacetonate under nitrogen at 420 - 450 °C, and is a brown translucent thermoplastic brittle solid with a softening point of 170 - 220 °C and an aluminum content of 0.5 - 1 wt%.
[0012] The number average molecular weight of the polycarbosilane is 450 - 800 Da.
[0013] The particle diameter of the boron nitride powder is usually in the nanometer range, but not limited thereto.
[0014] The boron nitride powder in step (1) is hexagonal boron nitride nanosheets or rod-shaped boron nitride.
[0015] The solvent in step (1) is either n-hexane or xylene.
[0016] The mass ratio of the polyaluminum carbosilane, boron nitride, and solvent in step (1) is 20:0.1 - 2:5 - 10.
[0017] The ball milling conditions in step (1) are: the ball milling time is 8 - 24 h, and the turntable speed is 300 rpm.
[0018] The melt spinning treatment in step (2) is: the spinning temperature is 320 - 380 °C, and the atmosphere is nitrogen.
[0019] In step (2), the infusibilization treatment is air thermal oxidation crosslinking, the temperature is 150 - 220°C, and the infusibilization time is 2 - 4 h, that is, heat treatment is carried out for 2 - 4 h in an air atmosphere at a temperature of 150 - 220°C.
[0020] In step (2), the high-temperature pyrolysis treatment is as follows: in a nitrogen atmosphere, the temperature is raised to 1100°C at a heating rate of 2 - 5°C / min and held for 0.5 - 2 h; the sintering densification treatment is as follows: in an argon atmosphere, the temperature is raised to 1700 - 1900°C at a heating rate of 5 - 10°C / min and held for 0.5 - 2 h.
[0021] In the preparation of the silicon boron carbonitride aluminum ceramic fiber of the present invention, in the presence of a solvent, polyaluminum carbosilane and boron nitride powder are used as raw materials, and a PACS / BN hybrid precursor is prepared by ball milling and blending. This method not only enables the uniform dispersion of BN in PACS, but also draws on the preparation route of aluminum-containing SiC ceramic fibers to realize the preparation of aluminum-containing SiBCN ceramic fibers, and the preparation process is relatively mature. Therefore, steps such as ball milling, melt spinning, infusibilization treatment, and high-temperature pyrolysis described in this method can all be operated in a conventional manner.
[0022] The beneficial effects of the present invention are specifically as follows:
[0023] (1) By means of ball milling and mixing, the present invention uniformly disperses boron nitride in polyaluminum carbosilane. Through melt spinning, infusibilization treatment, and high-temperature pyrolysis, the preparation of aluminum-containing SiBCN ceramic fibers is successfully realized, avoiding the use of highly toxic organic raw materials and difficult-to-synthesize PBSZ in conventional preparation methods. The reaction conditions are mild and the operation is simple.
[0024] (2) The addition amount of boron nitride powder takes into account both the forming performance of the precursor and the temperature resistance performance of the final ceramic fiber, realizing the adjustable boron and nitrogen contents of the ceramic fiber.
[0025] (3) The present invention realizes the densification of aluminum-containing SiBCN ceramic fibers by using an aluminum-doped sintering aid in combination with a high-temperature sintering process. Description of the Drawings
[0026] Figure 1 are SEM images of two forms of boron nitride powder in specific examples of the present invention: (a) flaky; (b) rod-shaped;
[0027] Figure 2 are optical photographs of each precursor in specific examples of the present invention: (a) PACS; (b) PACS / BN - 0.5%; (c) PACS / BN - 2%; (d) PACS / BN - 5%;
[0028] Figure 3 are infrared spectra of each precursor in specific examples of the present invention;
[0029] Figure 4 Optical photographs of the precursor filaments in specific embodiments of the present invention: (a) PACS; (b) PACS / BN-8%.
[0030] Figure 5 Optical photographs and SEM images of ceramic fibers obtained by pyrolysis at 1100 °C and sintering at 1850 °C in specific embodiments of the present invention: (a)(b)(c) 1100 °C; (d)(e)(f) 1850 °C;
[0031] Figure 6 SEM of Si-C-Al(O) ceramic fibers in the comparative example of the present invention. Detailed implementation manners
[0032] The present invention will be further described below in conjunction with specific examples.
[0033] Specific embodiments of the present invention are as follows:
[0034] Example 1
[0035] Preparation of the hybrid precursor PACS / BN (flake)-8%: Dissolve 20 g of polyaluminum carbosilane with a softening point of 170 - 220 °C in 9 g of n-hexane to form a polyaluminum carbosilane solution, add 1.6 g of hexagonal boron nitride nanosheets (whose SEM is as Figure 1 shown in a), and then place it in a ball mill jar and ball mill for 24 h. After the boron nitride powder is evenly dispersed in the polyaluminum carbosilane solution, the solvent is removed by distillation to obtain a uniform light yellow PACS / BN (flake)-8% hybrid precursor;
[0036] After the PACS / BN (flake)-8% hybrid precursor is melt-spun at 370 °C under a nitrogen atmosphere, a hybrid precursor fiber filament is obtained (the optical photograph of the filament is as Figure 4 shown in b, and it can be seen that the fiber diameter distribution is relatively uniform); the filament is infusibilized at 180 °C in air for 4 h to obtain an infusibilized fiber; the infusibilized fiber is heated to 1100 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and pyrolyzed for 1 h to obtain a fired fiber (the optical photograph and SEM of the fired fiber are as Figure 5 shown in a and 5b, 5c); the fired fiber is heated to 1850 °C at a heating rate of 10 °C / min under an argon atmosphere and held for 0.5 h to obtain a black, relatively dense aluminum-containing SiBCN ceramic fiber (its optical photograph and SEM are as Figure 5 shown in d and 5e, 5f). Due to the addition of boron nitride, the finally provided aluminum-containing SiBCN ceramic fiber is a black and dull filament bundle with a diameter of about 32 μm, and the structure is uniform and dense, which further shows that boron nitride has good dispersibility in polyaluminum carbosilane.
[0037] Example 2
[0038] Preparation of the hybrid precursor PACS / BN-5%: Dissolve 20 g of polyaluminum carbon silicon alkane with a softening point of 170 - 220 °C in 8 g of n-hexane to form a polyaluminum carbon silicon alkane solution. After adding 1 g of hexagonal boron nitride nanosheets, place it in a ball milling jar and ball mill for 24 h. After the boron nitride powder is evenly dispersed in the polyaluminum carbon silicon alkane solution, distill off the solvent to obtain a uniform light yellow PACS / BN-5% hybrid precursor (its optical photograph is as Figure 2 shown in d. It can be seen that the color of the precursor is uniform, indicating that the boron nitride is relatively evenly dispersed in the polyaluminum carbon silicon alkane; from Figure 3 it can be known that in the prepared hybrid precursor PACS / BN-5%, except for the infrared characteristic peak of B-N, no other characteristic peaks appear, indicating that there is only a simple physical mixture between the polyaluminum carbon silicon alkane and the boron nitride);
[0039] After the PACS / BN-5% hybrid precursor is melt-spun at 330 °C under a nitrogen atmosphere, a hybrid precursor fiber filament is obtained; the filament is infusibilized at 180 °C in air for 4 h to obtain an infusibilized fiber; the infusibilized fiber is heated to 1100 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and pyrolyzed for 1 h to obtain a fired fiber; the fired fiber is heated to 1850 °C at a heating rate of 10 °C / min under an argon atmosphere and held for 0.5 h to obtain a black, dense aluminum-containing SiBCN ceramic fiber.
[0040] Example 3
[0041] Preparation of the hybrid precursor PACS / BN-2%: Dissolve 20 g of polyaluminum carbon silicon alkane with a softening point of 170 - 220 °C in 7 g of n-hexane to form a polyaluminum carbon silicon alkane solution. After adding 0.4 g of hexagonal boron nitride nanosheets, place it in a ball milling jar and ball mill for 24 h. After the boron nitride powder is evenly dispersed in the polyaluminum carbon silicon alkane solution, distill off the solvent to obtain a uniform light yellow PACS / BN-2% hybrid precursor (its optical photograph is as Figure 2 shown in c);
[0042] After the PACS / BN-2% hybrid precursor is melt-spun at 310 °C under a nitrogen atmosphere, a hybrid precursor fiber filament is obtained; the filament is infusibilized at 180 °C in air for 4 h to obtain an infusibilized fiber; the infusibilized fiber is heated to 1100 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and pyrolyzed for 1 h to obtain a fired fiber; the fired fiber is heated to 1850 °C at a heating rate of 10 °C / min under an argon atmosphere and held for 0.5 h to obtain a black, dense aluminum-containing SiBCN ceramic fiber.
[0043] Example 4
[0044] Preparation of hybrid precursor PACS / BN-0.5%: 20 g of polyaluminum carbon silicon alkane with a softening point of 170-220 °C was dissolved in 5 g of n-hexane to form a polyaluminum carbon silicon alkane solution. After adding 0.1 g of hexagonal boron nitride nanosheets, it was placed in a ball mill jar and ball milled for 24 h. After the boron nitride powder was evenly dispersed in the polyaluminum carbon silicon alkane solution, the solvent was removed by distillation to obtain a uniform light yellow PACS / BN-0.5% hybrid precursor (its optical photograph is as shown in Figure 2 Figure b);
[0045] After the PACS / BN-0.5% hybrid precursor was melt-spun at 290 °C under a nitrogen atmosphere, a hybrid precursor fiber filament was obtained; the filament was infusibilized at 180 °C in air for 4 h to obtain an infusibilized fiber; the infusibilized fiber was heated to 1100 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and pyrolyzed for 1 h to obtain a fired fiber; the fired fiber was heated to 1850 °C at a heating rate of 10 °C / min under an argon atmosphere and held for 0.5 h to obtain a black, dense aluminum-containing SiBCN ceramic fiber.
[0046] Example 5
[0047] Preparation of hybrid precursor PACS / BN (rod-shaped)-8%: 20 g of polyaluminum carbon silicon alkane with a softening point of 170-220 °C was dissolved in 9 g of n-hexane to form a polyaluminum carbon silicon alkane solution. After adding 1.6 g of rod-shaped boron nitride powder (SEM is as shown in Figure 1 Figure b), it was placed in a ball mill jar and ball milled for 24 h. After the boron nitride powder was evenly dispersed in the polyaluminum carbon silicon alkane solution, the solvent was removed by distillation to obtain a uniform light yellow PACS / BN (rod-shaped)-8% hybrid precursor;
[0048] After the PACS / BN (rod-shaped)-8% hybrid precursor was melt-spun at 370 °C under a nitrogen atmosphere, a hybrid precursor fiber filament was obtained; the filament was infusibilized at 180 °C in air for 4 h to obtain an infusibilized fiber; the infusibilized fiber was heated to 1100 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and pyrolyzed for 1 h to obtain a fired fiber; the fired fiber was heated to 1850 °C at a heating rate of 10 °C / min under an argon atmosphere and held for 0.5 h to obtain a black, dense aluminum-containing SiBCN ceramic fiber.
[0049] Comparative Example 1
[0050] 20 g of polyaluminum carbon silicon alkane with a softening point of 170-220 °C was dissolved in 9 g of n-hexane to form a polyaluminum carbon silicon alkane solution. Without adding boron nitride powder, it was placed in a ball mill jar and ball milled for 24 h to obtain a uniform and transparent PACS solution. After the PACS solution was distilled to remove n-hexane, a brownish-yellow transparent precursor PACS (its optical photograph is as shown in Figure 2 Figure a) was obtained.
[0051] After the precursor PACS was melt-spun at 320 °C under nitrogen protection, precursor fiber rovings were obtained (the optical photograph of the rovings is as shown in Figure 4 Figure a). The rovings were infusibilized at 180 °C in air for 4 h to obtain infusibilized fibers; the infusibilized fibers were heated to 1100 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and pyrolyzed for 1 h to obtain sintered fibers; the sintered fibers were heated to 1900 °C at a heating rate of 10 °C / min in an argon atmosphere and held for 0.5 h to obtain porous Si-C-Al(O) ceramic fibers with a diameter of about 8 μm (the SEM of which is as shown in Figure 6 Figure).
[0052] Comparative Example 2
[0053] Preparation of the hybrid precursor PACS / BN-10%: 20 g of polyaluminum carbon silicon alkane with a softening point of 170 - 220 °C was dissolved in 10 g of n-hexane to form a polyaluminum carbon silicon alkane solution. After adding 2 g of hexagonal boron nitride nanosheets, it was placed in a ball mill jar and ball milled for 24 h. After the boron nitride powder was evenly dispersed in the polyaluminum carbon silicon alkane solution, the solvent was removed by distillation to obtain a uniform pale yellow PACS / BN-10% hybrid precursor;
[0054] The PACS / BN-10% hybrid precursor was melt-spun at 360 °C in a nitrogen atmosphere, and rovings could be extruded. However, due to the presence of boron nitride and a large addition amount, the rovings were brittle and could not be wound.
[0055] As can be seen from the above, in the present invention, boron nitride was introduced and evenly dispersed in polyaluminum carbon silicon alkane, and through specific processes such as melt spinning, infusibilization treatment, and high-temperature pyrolysis in sequence, the preparation of aluminum-containing SiBCN ceramic fibers was successfully realized, improving the forming performance of the precursor and the temperature resistance of the final ceramic fibers, and enabling the adjustment of the boron and nitrogen contents and densification of the ceramic fibers.
[0056] Therefore, the present invention uses a hybrid precursor of PACS and BN blending to prepare aluminum-containing SiBCN ceramic fibers. Through the processes of adding aluminum sintering aids, air infusibilization, and high-temperature sintering, the densification of the ceramic fibers is achieved, avoiding the use of toxic organic raw materials (such as boron trichloride, chlorosilane, and hexamethyldisilazane, etc.) or using difficult-to-synthesize polyborosilazane (PBSZ, the precursor of SiBCN ceramic fibers) as raw materials. It has the advantages of simple and safe operation, economy, mild reaction conditions, adjustable boron and nitrogen contents, etc., and has achieved outstanding and significant technical effects and advantages.
[0057] The above specific embodiments are used to explain and illustrate the present invention, rather than limiting the present invention. Any modifications and changes made to the present invention within the spirit and scope of the claims of the present invention fall within the protection scope of the present invention.
[0058] The above are only the preferred embodiments of the present invention. Therefore, any equivalent changes or modifications made according to the structures, features, and principles described in the scope of the patent application of the present invention are included in the scope of the patent application of the present invention.
Claims
1. A method for preparing aluminum-containing SiBCN ceramic fiber, characterized in that: (1) Preparation of hybrid precursor: polyaluminocarbosilane is dissolved in a solvent to form a polyaluminocarbosilane solution, boron nitride powder is added and the solution is ball-milled in a ball mill, and after the boron nitride powder is evenly dispersed in the polyaluminocarbosilane solution, the solvent is removed by distillation to obtain a uniform light yellow PACS / BN hybrid precursor; (2) The PACS / BN hybrid precursor in step (1) is subjected to four steps of melt spinning, infusible treatment, high temperature pyrolysis and sintering densification in sequence to obtain black aluminum-containing SiBCN ceramic fibers.
2. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: The polyaluminocarbosilane in step (1) is obtained by direct polymerization of polycarbosilane and aluminum acetylacetonate under nitrogen at 420-450°C.
3. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: The boron nitride powder in step (1) is hexagonal boron nitride nanosheets or rod-shaped boron nitride.
4. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: The solvent in step (1) is either n-hexane or xylene.
5. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: The mass ratio of polyaluminocarbosilane, boron nitride and solvent in step (1) is 20:0.1-2:5-10.
6. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: The ball milling conditions in step (1) are as follows: the ball milling time is 8 to 24 hours and the turntable speed is 300 rpm.
7. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: The melt spinning process in step (2) is as follows: the spinning temperature is 320-380° C., and the atmosphere is nitrogen.
8. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: The infusibility treatment in step (2) is air thermal oxidation cross-linking, the temperature is 150-220° C., and the infusibility time is 2-4 hours.
9. The method for preparing aluminum-containing SiBCN ceramic fiber according to claim 1, characterized in that: In the step (2), the high temperature pyrolysis treatment is: in a nitrogen atmosphere, the temperature is increased to 1100° C. at a heating rate of 2 to 5° C. / min and kept warm for 0.5 to 2 hours; the sintering densification treatment is: in an argon atmosphere, the temperature is increased to 1700 to 1900° C. at a heating rate of 5 to 10° C. / min and kept warm for 0.5 to 2 hours.
10. An aluminum-containing SiBCN ceramic fiber, characterized in that: The invention is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Silicon carbide fibers having a low oxygen content and a preparing method thereof
CN108035014A
Si-Al-C-O fiber preparation method
CN109111574A
Boron-aluminum-doped polycarbosilane as well as preparation method and application thereof
CN116333322A
Silicon carbide fiber having boron nitride layer in fiber surface and process for the production thereof
US20050064189A1